Dual Intratumoral Redox/Enzyme‐Responsive NO‐Releasing Nanomedicine for the Specific, High‐Efficacy, and Low‐Toxic Cancer Therapy. Issue 30 (11th June 2018) - Jia, Xiaobo; Zhang, Yihua; Zou, Yu; Wang, Yao; Niu, Dechao; He, Qianjun; Huang, Zhangjian; Zhu, Weihong; Tian, He; Shi, Jianlin; Li, Yongsheng
Abstract: Chemotherapy suffers numbers of limitations including poor drug solubility, nonspecific biodistribution, and inevitable adverse effects on normal tissues. Tumor‐targeted delivery and intratumoral stimuli‐responsive release of drugs by nanomedicines are considered to be highly promising in solving these problems. Compared with traditional chemotherapeutic drugs, high concentration of nitric oxide (NO) exhibits unique anticancer effects. The development of tumor‐targeting and intratumoral microenvironment‐responsive NO‐releasing nanomedicines is highly desired. Here a novel kind of organic–inorganic composite nanomedicine (QM‐NPQ@PDHNs) is presented by encapsulating a glutathione S ‐transferases π (GSTπ)‐responsive drug O 2 ‐(2, 4‐dinitro‐5‐[2‐(β‐d ‐galactopyranosyl olean‐12‐en‐28‐oate‐3‐yl)‐oxy‐2‐oxoethyl] piperazine‐1‐yl phenyl) 1‐(methylethanolamino)diazen‐1‐ium‐1, 2‐dilate (NPQ) as NO donor and an aggregation‐induced‐emission (AIE) red fluorogen QM‐2 into the cores of the hybrid nanomicelles (PEGylated disulfide‐doped hybrid nanocarriers (PDHNs)) with glutathione (GSH)‐responsive shells. The QM‐NPQ@PDHN nanomedicine is able to respond to the intratumoral over‐expressed GSH and GSTπ, resulting in the responsive biodegradation of the protective organosilica shell and NPQ release, and subsequent NO release within the tumor, respectively, and thus normal organs remain unaffected. This work demonstrates a paradigm of dual intratumoral redox/enzyme‐responsive NO‐release nanomedicine for tumor‐specific and high‐efficacy cancer therapy. Abstract : A dual‐responsive nanomedicine is facilely constructed by encapsulating the glutathione S ‐transferases (GSTπ)‐responsive nitric oxide (NO)‐prodrug into the cores of the redox‐responsive nanocarriers, which can release NO when stimulated by the tumor‐overexpressed glutathione (GSH) and GSTπ. Its therapeutic efficacy on cancer cells and safety on normal cells are guaranteed with the combination of its dual‐responsive feature and its passively targeted accumulation performance in tumor sites.